Candidate Sites for Millimeter and Submillimeter Ground-Based Telescopes: Atmospheric Rating for the Eurasian Submillimeter Telescopes Project - Artem Y. Shikhovtsev; Pavel G. Kovadlo; Philippe Baron (Sensors)
Modern sensing technologies used in the field of ground-based telescopes still present several challenges. First of all, these challenges are associated with the development of new-generation instruments for astronomical observations and with the influence of Earth’s atmosphere on radiation in various ranges of the electromagnetic spectrum. The atmosphere is often the main factor determining the technical characteristics of the instruments in both the optical and millimeter ranges. In particular, for millimeter/submillimeter telescopes, water vapor is the main gas that determines atmospheric opacity. The correct assessment of water vapor makes it possible to estimate the optical opacity of the atmosphere and, on this basis, the capabilities of the millimeter/submillimeter telescope and the limitations of its use in the mode of very long baseline interferometry. Many studies seek to effectively characterize water vapor content and dynamics for site-testing purposes regarding ground-based millimeter and submillimeter telescope application. In the present article, we study the water vapor content within a fairly large region, which has been poorly covered in the modern literature. Based on the ERA-5 reanalysis data as a site-testing-oriented tool, we obtained spatial distributions of the precipitable water vapor (PWV) within a large region (<semantics>20∘<mspace width="3.33333pt"></mspace>N</semantics>–<semantics>70∘<mspace width="3.33333pt"></mspace>N</semantics>, <semantics>35∘<mspace width="3.33333pt"></mspace>E</semantics>–<semantics>120∘<mspace width="3.33333pt"></mspace>E</semantics>). These distributions of PWV were corrected with respect to the characteristic vertical scale of water vapor <semantics>Heff</semantics> and the relative height difference in the grid nodes in the ERA-5. The calculated values of PWV are highly correlated with the Global Navigation Satellite System-derived PWV, with Pearson coefficients greater than 0.9. Using the refined estimations, we determined the median values of atmospheric opacities corresponding to new prospective sites (Khulugaisha Peak and Tashanta) as well as the Special Astrophysical Observatory (the key astronomical observatory in Russia). Together with Ali in China, Khulugaisha Peak and Tashanta are considered by us as potential sites for the placement of a millimeter/submillimeter telescope within the framework of the project of the Eurasian Submillimeter Telescopes. The results obtained in this paper suggest promising atmospheric conditions for astronomic observations, at least in the millimeter range. In particular, we believe that this study will be a basis for the Eurasian Submillimeter Telescopes (ESMT) project, within the framework of which it is assumed to create a number of ground-based millimeter/submillimeter telescopes.